Penerapan Dekonstruksi dalam Perancangan Bangunan Cinema Complex di Kabupaten Garut - Euis Puspita Dewi; Dena Rahmana; Siti Sujatini (Fakultas Teknik Universitas Persada Indonesia YAI, 2022)
The purpose of this research is to apply the concept of Deconstruction Architecture to the designof the Cinema Complex in Garut Regency. The Cinema Complex is a cinema building which isalso facilitated by other functions, so that it is accommodating to conditions that are facingrecovery towards the Covid 19 Pandemic. The world of entertainment and the community is anecessity to overcome boredom, which during the pandemic imposed restrictions on mostactivities. In Garut Regency, the existence of the Cinema Complex is something new. With the highpotential of young people, a different and up-to-date Cinema Complex design is needed. Therefore,the Deconstruction approach is very suitable to be applied in the design of the building form.Through this approach, it is expected to produce a Cinema Complex building that can become acity icon and provide passion for the community after the pandemic.